Analysis and Comparison of Methods for Determining Small Piles of Wood Chips Using Laser Scanning Technology - Miloš Gejdoš; Martin Lieskovský; Michal Ferenčík (BioResources)
The monitoring of forest biomass stock volumes in larger operations is typically conducted irregularly, either by tracking cargo arrivals or by using simple manual measurement methods. The objective of this study was to assess the accuracy of smart methods based on laser scanning technology, integrated into mobile phones and a handheld laser scanner, for measuring smaller piles of forest chips. For the experiment, a total of 50 m³ of fiberwood logs were chipped and distributed into four piles. The smart solutions selected for laser scanning of forest biomass in this study were the Stonex Geoslam X120 GO handheld laser scanner and the iPhone 14 Pro Max equipped with a LiDAR sensor. The results were influenced by the selected conversion coefficient and the exclusion of small scattered fragments of forest chips around the piles, which were not included in the final volume calculation. The smallest discrepancy identified by the smart solutions was 3 m³ (6%) of woody mass. The findings demonstrated that the smart solutions utilizing LiDAR technology offer good affordability, ease of use, and satisfactory accuracy. They are user-friendly and provide quick results.